Preventive Effects of β-Cryptoxanthin, a Potent Antioxidant and Provitamin A Carotenoid, on Lifestyle-Related Diseases-A Central Focus on Its Effects on Non-Alcoholic Fatty Liver Disease (NAFLD) - Azusa Nishino; Takashi Maoka; Hiroyuki Yasui (MDPI AG, 2021)
Humans usually get dietary carotenoids from foods such as green and yellow vegetables and algae. Carotenoids have been reported to effectively reduce the risk of developing lifestyle-related diseases. β-Cryptoxanthin, which is an antioxidative carotenoid and a type of provitamin A, is metabolically converted to vitamin A. β-Cryptoxanthin has recently gained attention for its risk-reducing effects on lifestyle-related diseases, especially on non-alcoholic fatty liver disease (NAFLD), from epidemiological, interventional, and mechanistic studies. Retinoids (vitamin A) have also been reported to be useful as a therapeutic agent for NAFLD. Provitamin A is known to serve as a supply source of retinoids through metabolic conversion by the regulated activity of β-carotene 15,15'-monooxygenase 1 (BCMO1) to the retina only when retinoids are deficient. From mechanistic studies using NAFLD-model mice, β-cryptoxanthin has been shown to contribute to the improvement of NAFLD through a multifaceted approach, including improved insulin resistance, suppression of oxidative stress and inflammation, a reduction of macrophages and a shift of their subsets, and control of lipid metabolism by peroxisome proliferator-activated receptor (PPAR) family activation, which are also expected to have clinical applications. β-Cryptoxanthin has the potential to prevent lifestyle-related diseases from different angles, not only as an antioxidant but also as a retinoid precursor.